Influência da densidade da cobertura vegetal sobre a comunidade de abelhas solitárias (Hymenoptera, Aculeata) que nidificam em cavidades pré-existentes em áreas de mata da baixada maranhense, Amazônia Oriental - MUNIZ, David Barros (2015)
In the present study, we investigated the influence of the density of vegetation cover on the community of solitary bees (Hymenoptera, Aculeata) that nidificate in preexisting cavities. The survey was conducted in three forest areas located in the “Environmental Protection Area of Baixada Maranhense”, in the cities of Peri Mirim, Penalva and Vitória do Mearim. Solitary bees were sampled using the trap-nest method during the period of August 2013 to July 2014. Each area was sampled by three transects of 500 meters, and each transect was composed by six sample sets, with 12 trap-nests, totaling 216 trap-nests by area. The trap-nest occupations were analyzed regarding scale area, scale transects and scale sample set. The similarity index of Jaccard for the composition of species was of 28% between the areas of Peri Mirim and Vitória do Mearim, 34% between Penalva and Vitória do Mearim and 47% between Peri Mirim and Penalva. The abundance distribution of species was similar between the areas, with one abundant specie and many rare species, and did not differ statistically of the logarithmic series distribution. The greatest richness estimated was in the area of Vitória do Mearim with 32 spp. (ICE) and the smaller richness was in the area of Peri Mirim with 11 spp. (ACE). We observed an association of increasing richness and abundance of bees and vegetation cover in the scale area; we found a strong relationship between vegetation cover, the richness and abundance of Megachile species in the transect scale, but no relationship was found at sample set scale. The studied region presented a rich and diversified fauna of solitary bees that nidificate in trap-nests, with emphasis to the subfamily Megachilinae. The method proved to be robust and can be used for planning studies with trap-nests and conservation actions for these species. The maintenance of landscape unities in the “Baixada Maranhense” and of the vegetation typologies comprised by them is important for the biodiversity conservation of the Maranhão’s Amazon forest.